The Semantic Indication of the Item (Quds) in the Holy Qur’an - Al-sauaada, Mohammad; Al-sauaada, Aisha (Jordan Journal of Islamic Studies, 2023)
This study sheds light with the item (holiness) in the Holy Qur’an and studies it with a semantic contextual study, With the aim of disclosing the changes of this article, highlighting the utterances close to its pronouncement, recognizing the differences between them, showing its meaning in the context of the verses in which they are mentioned, and proving the meaning of each word in its context in which it is mentioned, Which reveals an important tributary of the Quranic miracles. The study revealed that the material had its linguistic meaning in the Qur’anic usage as appropriate to the context, and that it cannot be replaced by another word, whatever it's close in meaning, through an inductive and analytical study of this artical.